Psychosocial factors affecting mental well-being of dental students: a qualitative study - Lim, Shea Lee; Mohamed Ludin, Salizar; Abu Bakar, Noraini; Ahmad Basri, Nadzirah (International Islamic University Malaysia, 2024)
Dental students often faced high levels of mental distress which contributed to lower mental well-being. This has a negative impact on their health and academic performance. Many previous studies focused on students who were already in a 'diseased' state with little focus on students who are well but at risk of developing poor mental well-being. A better understanding of the factors affecting the mental well-being dental students is needed. This study was aimed to explore the factors associated with mental well-being of dental students and to identify steps to promote their mental well-being. MATERIALS & METHODS: In this qualitative study, individual interviews were conducted among undergraduate dental students using semi-structured interview guide. The interviews were recorded, transcribed via verbatim and analyzed using thematic analysis. RESULTS: The analysis revealed three main themes; i) Impression of dentistry, ii) Stressors and iii) Mental health experience. This study elucidated the experiences and stressors of dental students as they advanced through their dental education especially in clinical years. Most of the students had experienced low levels of mental well-being which affected them negatively. The findings also showed opportunities for fostering better mental well-being. CONCLUSION: Undergraduate dental students often experienced low mental well-being due to the stressors they faced. Identifying the factors that influenced the mental well-being of dental students would allow for early intervention and fostering of mental well-being among dental students.